Implementasi Pembelajaran Al-Qur'an Hadis di MAN 2 Karawang: Analisis Hambatan dan Solusi Pembelajaran - Rahmah Diara; Mutiara Ramadhani Alfitriah; Muthliq Febrily Albachaj; Siti Nenk Lawati; Amelia Khoirunnisa; Sihabudin (Jurnal Miftahul Ilmi: Jurnal Pendidikan Agama Islam, 2026)
The purpose of this study was to analyze the implementation of Al-Qur’an and Hadith teaching at MAN 2 Karawang, including the challenges faced and approaches to resolving them. The method used was qualitative with a descriptive approach. Information was collected through interviews and documentation with the principal, Al-Qur’an and Hadith teachers, and eleventh-grade students. The research findings indicate that teaching is conducted in accordance with the madrasah curriculum, using a thematic and contextual approach that focuses on moral development and the application of Islamic values in daily life. Teachers use various methods, such as lectures, discussions, questions and answers, and hadith memorization. However, the teaching and learning process still faces several obstacles, such as a lack of infrastructure, including projectors, limited availability of textbooks, and unsupportive classroom conditions, which affect students’ concentration. Several solutions implemented include the gradual provision of facilities, the use of digital technology through students’ mobile phones and e-books, and the implementation of more interactive teaching methods to increase student motivation.